Propuesta de procesos en la producción de alimentos para truchas (ONCORHYNCHUS MYKISS) en base a desperdicios cárnicos. - Quishpe Loachamin, Jenny Paola (2020)
In the Metropolitan camal from Quito are slaughted nearly of 1095 bovines weekly which carries to an ambient pollution in the air as in the ground and rivers that through sewerage is sent the liquid waste. This situation has been worrying because with it also comes illnesses that affects the health of its population. Found the massive pollution problem, a possible solution could be use those meat waste from the slaughter done every single day to make food for the specie Oncorhynchus Mykiss, this animal requires of certain nutritional parameters to its good development because of it has been researched documentary that it could be made bovine’s blood flour that through an ideal process it will obtain a flour with the 80-82% of protein, this parameter is inside the nutritional square and it could become in food. From the analysis done, the accurate process for the blood flour elaboration is with an argentine technology which is very sustentaible and friendly with the environment that does the whole process automatically with an only operator, this machine can work 24 hours a day, the process is by atomization or called Spray Dryer which gives as a result an homogenic flour and bacteria free. On the other hand, to make pellets is needed the Extrusion Process in which is obtained the suflation which allows that the food can float on the water in the way that the Oncorhynchus Mykiss can eat it completely without wasting it. The modality of this project belongs to feasible project, which is meant, bibliography researching. The theoretical framework as fundamental category in the elaboration process of flour and the extrusion process to make pellets.